A small-pitch thick copper plate and a processing method thereof
Patent Information
- Application Number
- CN202611267744.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]有鉴于此,本申请提供一种小间距厚铜板及其加工方法,用于解决如何在制备厚铜小间距PCB过程中兼顾刻蚀效率和控制侧蚀的问题
本申请通过将BTA缓蚀剂与两种微胶囊复配于同一蚀刻液中,喷淋刻蚀时,喷淋液流垂直冲击线路底部,两种微胶囊于底部原位破裂,在解除缓蚀剂对底部刻蚀的抑制的同时使底部铜面保持高刻蚀速率,而线路侧壁受喷淋液流平行冲刷,微胶囊保持完整不破裂,BTA得以持续吸附于侧壁铜表面发挥缓蚀作用,从而在同一刻蚀步骤中实现了底部高速刻蚀和侧蚀控制,最终得到厚铜小间距PCB产品。
Smart Images

Figure CN122995038A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of PCB technology, and in particular to a small-pitch thick copper plate and its processing method. Background Technology
[0002] With the increasing demands for PCB current carrying capacity in fields such as new energy vehicles and high-power power supplies, the application of thick copper PCBs is becoming more and more widespread. Thick copper can effectively reduce line resistance, reduce heat generation, and improve current carrying capacity. At the same time, electronic devices are developing towards miniaturization and high integration, requiring more refined PCB lines. The line spacing has generally been reduced to 3.5mil. Therefore, it is very important to manufacture thick copper small-pitch PCB products.
[0003] However, in related technologies, to prepare a thick copper layer, the etching time needs to be extended to ensure complete etching. The extension of the etching time inevitably exacerbates the lateral erosion of the circuit sidewalls by the etching solution, i.e., side etching, which leads to a reduction in circuit width and a deformation of the spacing. In severe cases, it can cause open circuits or short circuits. Increasing the concentration of the etching inhibitor can help overcome side etching, but it will affect the etching efficiency at the bottom. The two requirements of thick copper and small spacing have created a technical contradiction in the etching process, which directly restricts the product yield and mass production of thick copper small-pitch PCBs.
[0004] Therefore, it is very important to provide a technical solution that balances etching efficiency and control of side etching during the fabrication of thick copper small-pitch PCBs. Summary of the Invention
[0005] In view of this, this application provides a small-pitch thick copper plate and its processing method to solve the problem of balancing etching efficiency and controlling side etching during the fabrication of thick copper small-pitch PCBs.
[0006] To achieve the above technical objectives, this application adopts the following technical solution: In a first aspect, this application provides a method for processing small-pitch thick copper plates, comprising the following steps: S1. Provide copper-clad laminate substrate and perform the first full-board electroplating on the substrate; S2. Perform the first pattern transfer, apply the first dry film to the board surface, and after exposure and development, retain the dry film on the circuit pattern to expose the gap area that needs to be etched away. S3. Use an etching solution to perform spray etching and remove the first dry film; S4. Fill the etched gaps with insulating resin, cure it, and grind it smooth; S5. Perform a second pattern transfer, apply a second dry film, and after exposure and development, the dry film covers the gap area, exposing the circuit pattern; S6. Perform the second pattern electroplating; S7. Remove the second dry film to obtain a small-pitch thick copper plate; The etching solution comprises the following components in parts by weight: 180-200 parts copper chloride, 1.8-2.5 parts hydrochloric acid, 4-8 parts benzotriazole corrosion inhibitor, 1-5 parts first microcapsule, 1-5 parts second microcapsule, 0.3-0.7 parts surfactant, 0.2-0.6 parts dispersant, 0.1-0.3 parts wetting agent, and 0.5-2.0 parts stabilizer; the core material of the first microcapsule contains β-cyclodextrin-polyethylene glycol; the core material of the second microcapsule contains copper peroxide.
[0007] Preferably, the molar ratio of β-cyclodextrin-polyethylene glycol (based on β-cyclodextrin units) in the first microcapsule core material to copper peroxide in the second microcapsule core material is 1:1-2.
[0008] Preferably, the wall material of the first microcapsule is calcium alginate, and the wall material of the second microcapsule is polyethylene glycol.
[0009] Preferably, the surfactant is polyethylene glycol; the dispersant is triethanolamine; the wetting agent is sodium 2-ethylhexanol sulfate; and the stabilizer is urea.
[0010] Preferably, the first microcapsule is prepared by using a β-cyclodextrin-polyethylene glycol aqueous solution as the inner aqueous phase and a sodium alginate aqueous solution as the outer aqueous phase, through a double emulsion-calcium ion crosslinking method.
[0011] Preferably, the second microcapsule is prepared by using copper peroxide as the core material, polyethylene glycol as the wall material, and sodium sulfate aqueous solution as the coagulant, through a single coagulation method.
[0012] Preferably, the method further includes the step: S8. Repeat steps S4-S7.
[0013] Preferably, in step S3, the spray pressure for spray etching is 0.2-0.4 MPa, the temperature is 45-55℃, and the etching time is 2-4 minutes.
[0014] Secondly, this application provides a small-pitch thick copper plate.
[0015] Preferably, the thickness of the copper plates is greater than or equal to 70 μm, and the spacing is less than or equal to 150 μm.
[0016] The beneficial effects of this application are as follows: This application combines BTA corrosion inhibitor with two types of microcapsules in the same etching solution. During spray etching, the spray flow vertically impacts the bottom of the circuit, causing the two types of microcapsules to rupture in situ at the bottom. This relieves the inhibition of bottom etching by the corrosion inhibitor while maintaining a high etching rate on the bottom copper surface. Meanwhile, the sidewalls of the circuit are scoured by the parallel spray flow, keeping the microcapsules intact and preventing them from rupturing. BTA can then be continuously adsorbed onto the sidewall copper surface to exert its corrosion inhibitor effect. Thus, high-speed bottom etching and side etching control are achieved in the same etching step, ultimately resulting in a thick copper small-pitch PCB product. Attached Figure Description
[0017] Figure 1 This is a schematic diagram of the preparation process for this scheme; Figure 2 This is a photograph of the product obtained in Example 1. Detailed Implementation
[0018] The embodiments of the technical solution of this application will be described in detail below. The following embodiments are only used to illustrate the technical solution of this application more clearly, and are therefore only examples, and should not be used to limit the scope of protection of this application.
[0019] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.
[0020] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0021] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0022] Unless otherwise explicitly defined and specified herein, all technical and scientific terms used in this application shall have the generally accepted meanings understood by one of ordinary skill in the field of chemical and chemical materials technology (including but not limited to polymer chemistry, inorganic chemistry, organic synthesis, catalysis chemistry, materials processing, and chemical unit operations) based on their professional knowledge and conventional practice. The use of any terminology herein is intended to describe the specific embodiments of this application in the clearest and most accurate manner, so as to fully disclose the technical solution. Such use shall not in any way be construed as a limitation on the scope of the claims, nor does it imply the exclusion of equivalent technical solutions that could be reasonably known by one of skill in the art based on the concept of this application.
[0023] The terms "comprising," "including," "having," "containing," and any grammatical variations or similar expressions used in the specification and claims of this application are all open-ended and non-exhaustive descriptive terms. Their purpose is to explicitly describe the existence of technical features, components, steps, or parts, while explicitly allowing and covering the possibility that other features, components, steps, parts, or any combinations thereof not explicitly listed may exist or be added to the technical solution, as long as such additions do not destroy the integrity and inventiveness of the original technical solution.
[0024] When the terms "embodiments," "some embodiments," or "specific embodiments" are mentioned in the specification, they refer to examples that, in conjunction with the specific parameters, materials, steps, and results described in that section, constitute one or a group of examples for implementing the technical solutions of this application. These embodiments are used for full disclosure and illustrative purposes, not for exhaustive enumeration. Those skilled in the art should understand that, without departing from the overall inventive concept of this application, the various technical features disclosed in different embodiments can be combined, substituted, modified, or deleted to form other implementation methods that are not listed one by one in the specification but also fall within the protection scope of this application.
[0025] Unless otherwise expressly specified and limited, all terms related to chemical process operations, material preparation, processing and analytical testing involved in this application shall be interpreted in the broadest sense based on the conventional understanding of those skilled in the art.
[0026] Regarding performance testing and structural characterization, all testing and characterization methods involved in this application, unless otherwise specified, refer to conventional methods known in the art. Specific testing conditions may be selected and adjusted according to the sample properties and relevant national standards, international standards, or industry-standard methods. Test items may include mechanical properties (such as tensile, bending, and impact strength), thermal properties (such as DSC and TGA analysis), and chemical stability (such as solvent resistance and acid / alkali corrosion resistance). Structural characterization methods may include FT-IR, NMR, XRD, SEM, TEM, and BET. All test results should be understood to be within the allowable range of conventional experimental errors.
[0027] Regarding numerical values and ranges, all parameter ranges expressed in this application in the form of "from a certain value to a certain value" should be understood as explicitly disclosing the endpoints of the range, each specific numerical point between the endpoints, and all sub-ranges formed by any two numerical points within the range. For example, "30℃ to 80℃" discloses 30, 31, ..., 80℃, as well as sub-ranges such as 30-50℃, 45-70℃, etc. When a numerical value is preceded by "about," "approximately," or similar words, it indicates that the numerical value is allowed to have reasonable errors recognized in the art under the measurement or control conditions, which can generally be understood as the deviation allowed by relevant standards or a normal fluctuation range of ±5% or ±10%.
[0028] This application provides a method for processing small-pitch thick copper plates, characterized by comprising the following steps: S1. Provide copper-clad laminate substrate and perform the first full-board electroplating on the substrate; S2. Perform the first pattern transfer, apply the first dry film to the board surface, and after exposure and development, retain the dry film on the circuit pattern to expose the gap area that needs to be etched away. S3. Use an etching solution to perform spray etching and remove the first dry film; S4. Fill the etched gaps with insulating resin, cure it, and grind it smooth; S5. Perform a second pattern transfer, apply a second dry film, and after exposure and development, the dry film covers the gap area, exposing the circuit pattern; S6. Perform the second pattern electroplating; S7. Remove the second dry film to obtain a small-pitch thick copper plate; The etching solution comprises the following components in parts by weight: 180-200 parts copper chloride, 1.8-2.5 parts hydrochloric acid, 4-8 parts benzotriazole corrosion inhibitor, 1-5 parts first microcapsule, 1-5 parts second microcapsule, 0.3-0.7 parts surfactant, 0.2-0.6 parts dispersant, 0.1-0.3 parts wetting agent, and 0.5-2.0 parts stabilizer; the core material of the first microcapsule contains β-cyclodextrin-polyethylene glycol; the core material of the second microcapsule contains copper peroxide.
[0029] This application achieves differentiated control of bottom etching and side etching by combining BTA corrosion inhibitor with two types of microcapsules in the same etching solution and utilizing the different fluid impact directions and stress magnitudes experienced by the bottom and sidewalls of the circuit during spray etching. The specific mechanism of action is as follows: During spray etching, the sprayed liquid impacts the bottom of the circuit vertically. The normal stress on the bottom reaches the rupture threshold of the microcapsule wall material, causing both types of microcapsules to rupture in situ at the bottom of the circuit. The first microcapsule releases β-cyclodextrin-polyethylene glycol (β-CD-PEG), which effectively peels off and encapsulates BTA molecules adsorbed on the Cu-BTA protective film on the bottom copper surface, exposing a fresh, active surface and thus relieving the inhibition of bottom etching by the BTA etching inhibitor. Simultaneously, the second microcapsule releases copper peroxide, which decomposes in the acidic etching solution environment to produce Cu. 2+ and reactive oxygen species, Cu 2+ The microcapsules replenish the copper ions consumed by the etching reaction in the localized bottom area, while the active oxygen rapidly oxidizes the exposed copper surface, significantly accelerating copper dissolution and greatly improving bottom etching efficiency. The synergistic effect of the two microcapsules achieves high-rate bottom etching while maintaining a high dosage of the corrosion inhibitor BTA.
[0030] On the other hand, the sidewalls of the circuit are subjected to parallel scouring by the sprayed liquid flow, and the shear stress on the sidewalls is far below the rupture threshold of the microcapsule wall material. Both types of microcapsules remain intact on the sidewalls, thus preventing the release of β-CD-PEG and copper peroxide from the sidewall region. Free BTA corrosion inhibitors in the etching solution are continuously adsorbed onto the copper surface of the sidewalls, reacting with Cu2O on the copper surface to form a stable Cu-BTA hydrophobic protective film, effectively inhibiting the lateral dissolution of copper on the sidewalls and thus controlling the side etching of the circuit. Furthermore, polymer fragments generated after the rupture of the wall materials of the first and second microcapsules can be partially adsorbed onto the sidewall surface during the liquid flow, forming an auxiliary physical shield for the sidewalls and further blocking Cl. - The corrosion resistance of corrosive ions enhances the sidewall's ability to resist lateral corrosion.
[0031] Therefore, this application successfully fabricated a thick copper small-pitch PCB product by improving the etching efficiency of the bottom and reducing the side etching during the etching process.
[0032] In some embodiments, the molar ratio of β-cyclodextrin-polyethylene glycol (based on β-cyclodextrin units) in the first microcapsule core material to copper peroxide in the second microcapsule core material is 1:1-2.
[0033] In this embodiment, both the β-cyclodextrin and polyethylene glycol portions of the β-cyclodextrin-polyethylene glycol complex undergo coordination reactions with copper ions, releasing β-CD-PEG that reacts with the Cu in the bottom region. 2+ After coordination, the resulting coordination structure enhances the exfoliation effect of BTA in the Cu-BTA film. Appropriately excessive amounts of copper peroxide can compensate for the effect of β-CD-PEG on Cu... 2+ On the one hand, it consumes coordination, and on the other hand, it ensures that enough copper peroxide decomposes to generate active oxygen to accelerate the dissolution of copper at the bottom.
[0034] In some embodiments, the wall material of the first microcapsule is calcium alginate, and the wall material of the second microcapsule is polyethylene glycol.
[0035] In this embodiment, both wall materials can rupture the microcapsules at a spray pressure of 0.2-0.4 MPa. After rupture at the bottom of the circuit, the resulting wall material fragments are submicron to micron in size. These fragments are suspended in the continuous flow of the sprayed solution and transported to various parts of the board surface, including the sidewalls of the circuit. The two types of fragments together form a physical shielding film, further blocking Cl. - The corrosion resistance of corrosive ions enhances the sidewall's ability to resist lateral corrosion. The fluid shear stress in the sidewall region is far below the rupture threshold of the microcapsule wall material. Therefore, the microcapsules adsorbed on the sidewall surface remain intact and do not rupture, preventing the release of β-CD-PEG and copper peroxide. The BTA corrosion inhibitor protective film on the copper surface of the sidewall is thus able to remain intact.
[0036] In some embodiments, the wall material thickness of the first microcapsule is 50-200 nm, and the wall material thickness of the second microcapsule is 50-200 nm.
[0037] In some embodiments, the particle size of the first microcapsule is 0.3-2 μm, and the particle size of the second microcapsule is 0.3-2 μm.
[0038] In some embodiments, the first microcapsule is prepared by using a β-cyclodextrin-polyethylene glycol aqueous solution as the inner aqueous phase and a sodium alginate aqueous solution as the outer aqueous phase, via a double emulsion-calcium ion crosslinking method.
[0039] In some embodiments, the material is prepared by a single coagulation method using copper peroxide as the core material, polyethylene glycol as the wall material, and sodium sulfate aqueous solution as the coagulant.
[0040] The above-described process for preparing microcapsules is a well-known method familiar to those skilled in the art, and those skilled in the art can adjust the raw material ratio and process parameters according to actual needs.
[0041] In this application, the preparation method of the first microcapsule is as follows: β-cyclodextrin-polyethylene glycol (β-CD-PEG) is dissolved in deionized water to prepare a β-CD-PEG aqueous solution with a mass percentage concentration of 5%-20% as the inner aqueous phase (W1). Sodium alginate is dissolved in deionized water to prepare a sodium alginate aqueous solution with a mass percentage concentration of 0.5%-2.0% as the outer aqueous phase (W2), and a nonionic emulsifier (such as Tween-80) accounting for 0.5%-2.0% of the mass of the outer aqueous phase is added. The inner aqueous phase is slowly added to the oil phase at a stirring speed of 5000-10000 r / min. The oil phase is liquid paraffin or vegetable oil, and the volume ratio of the inner aqueous phase to the oil phase is 1:3-1:8. Emulsification is continued for 30-60 seconds to form a W1 / O type primary emulsion. The above-mentioned pre-emulsion was slowly added to the external aqueous phase (sodium alginate aqueous solution) at a stirring speed of 2000-5000 r / min, with a volume ratio of pre-emulsion to external aqueous phase of 1:3-1:10. Emulsification was continued for 30-90 seconds to form a W1 / O / W2 type double emulsion. A 1%-5% (w / w) calcium chloride aqueous solution was slowly added dropwise to the resulting double emulsion under stirring, with a molar ratio of calcium ions to carboxyl groups in sodium alginate of 0.1:1-0.5:1. Stirring was continued at room temperature for 30-60 minutes to allow sodium alginate to cross-link and solidify with calcium ions at the oil-water interface, forming a calcium alginate capsule wall. After cross-linking, the capsule was centrifuged at 8000-12000 rpm for 10-15 minutes. The precipitate was washed 3-5 times with deionized water and dried in a vacuum drying oven at 40-50℃ to constant weight, yielding the first microcapsule product with an average particle size of 0.3-2 μm.
[0042] The preparation method of the second microcapsule is as follows: A certain amount of copper peroxide (CuO2) powder is weighed as the core material (the amount of copper peroxide is determined by calculating 1-2 times the molar amount of β-cyclodextrin units). Polyethylene glycol (PEG, molecular weight 4000-20000) and copper peroxide powder are premixed at a mass ratio of 3:1-5:1, added to deionized water, and heated and stirred in a 70℃ water bath until the polyethylene glycol is completely dissolved, forming a uniform PEG / CuO2 mixed suspension. Under the condition of stirring speed of 200-300 r / min, a coagulant solution (sodium sulfate aqueous solution, mass percentage concentration 15%-25%) is added dropwise to the above mixed suspension, and stirring is continued for 30-60 minutes, so that polyethylene glycol gradually precipitates on the surface of copper peroxide and coagulates into the capsule wall. After coagulation, the system is naturally cooled to room temperature, and stirring is continued for 10-20 minutes to fully solidify the capsule wall. The obtained microcapsule suspension was centrifuged (4000-6000 rpm, 10-15 minutes), the precipitate was washed repeatedly with deionized water 3-5 times, and dried in a vacuum drying oven at 40-50℃ to constant weight to obtain the second microcapsule product. The average particle size of the prepared second microcapsules was 0.3-2 μm.
[0043] In some embodiments, the surfactant is polyethylene glycol; the dispersant is triethanolamine; the wetting agent is sodium 2-ethylhexanol sulfate; and the stabilizer is urea.
[0044] The method for preparing the etching solution for small-pitch thick copper plates in this application is as follows: copper chloride is dissolved in deionized water accounting for 60-80% of the total volume and stirred until completely dissolved; hydrochloric acid is slowly added under stirring and stirred evenly; benzotriazole (BTA) is added and stirred until completely dissolved; surfactant, dispersant, wetting agent, and stabilizer are added and stirred until uniform; finally, the first microcapsule and the second microcapsule are added and stirred at a low speed of 100-300 rpm for 15-30 min to make the microcapsules uniformly dispersed; deionized water is added to the final volume and stirring at a low speed for 10-15 min is continued to obtain the solution, and the preparation temperature is controlled at 15-35℃.
[0045] like Figure 1 As shown, specifically, the method for preparing small-pitch thick copper plates using etching solution in this application is as follows: S1. Provide copper-clad laminate substrate and perform the first full-board electroplating on the substrate: The copper-clad laminate substrate is selected as FR-4 grade copper-clad laminate with an initial base copper thickness of 17μm. The full-board electroplating uses a copper sulfate system electroplating solution with a current density of 2.0-2.5A / dm³. 2 The electroplating time is determined according to the target copper thickness, and the copper layer thickness is increased to half of the target finished product thickness. During the electroplating process, the plating solution temperature is maintained at 25±2℃, and the uniformity of the plating solution is maintained by circulating filtration and air stirring. After the electroplating is completed, it is washed with water, pickled with acid, and dried. S2. Perform the first pattern transfer by applying the first dry film to the board surface. After exposure and development, retain the dry film on the circuit pattern, exposing the gap areas that need to be etched away. The dry film used is a photosensitive dry film with a thickness of 25-38μm. It is applied to the board surface using a hot press roller at a temperature of 100-120℃ and a pressure of 3-5kg / cm. 2 The speed is 1-2 m / min. After the film is applied, the board surface is exposed to the circuit pattern using an exposure machine with an exposure energy of 30-80 mJ / cm. 2 After exposure, the area is developed with a 1wt% sodium carbonate solution at a development temperature of 30±2℃ for 40-60 seconds to remove the dry film from the unexposed areas, exposing the gap areas that need to be etched away. The circuit pattern area is covered and protected by the dry film. After development, the area is washed with water and dried. S3. Use the etching solution of this application to perform spray etching and remove the first dry film; spray pressure 0.2-0.3MPa (i.e. 2-3bar), etching temperature 45-55℃, spray angle 45-60°, etching time 2-4 minutes; the spray etching equipment is a horizontal spray etching line, with independent pressure supply to the upper and lower spray pipes, and the nozzles are conical nozzles, arranged in an alternating pattern.
[0046] S4. Fill the etched gaps with insulating resin, cure, and grind smooth: Use a vacuum filling machine to fill the gaps formed by the first etching with epoxy resin. The resin is a commonly used liquid photosensitive epoxy resin filler in the PCB industry, with a viscosity of 2000-5000 cps at 25℃. Before filling, preheat the board surface to remove moisture, then perform vacuum filling under a vacuum degree ≤-0.095MPa, a filling pressure of 0.4-0.6MPa, and hold the pressure for 30-60 seconds. After filling, perform heat curing treatment at 150℃ for 60 minutes to ensure complete cross-linking and curing of the resin. After curing, grind the board surface using a non-woven fabric brush or non-woven fabric grinding wheel until the resin surface is flush with the copper surface. After grinding, wash and dry the board. S5. Perform the second pattern transfer, apply the second dry film, and after exposure and development, the dry film covers the gap area, exposing the circuit pattern: The second pattern transfer uses the same type of dry film as the first, and the film application, exposure, and development process conditions are the same as in step S2. It should be noted that the pattern design for the second pattern transfer is completely opposite to that of the first. After development, the dry film covers and protects all the gap areas filled with resin, while exposing the circuit pattern that requires thickened copper, ensuring that the copper for the second electroplating is deposited only in the circuit area and not in the gap area. After development, it is washed with water and dried. S6. Perform a second pattern plating and remove the second dry film: The second pattern plating uses a copper sulfate-based pattern plating solution with a current density of 2.0-3.0 A / dm³. 2 The electroplating time is determined based on the target copper thickness, increasing the copper thickness in the exposed circuit area from 35μm to the required thickness of the finished product (e.g., 70μm). During the electroplating process, no copper is deposited in the gap areas protected by the dry film. S7. After electroplating, the film is removed using a 3-5wt% sodium hydroxide solution at a temperature of 45-55℃. The second dry film protective layer is then peeled off. After removal, the film is washed with water, acid-washed, and dried.
[0047] In some embodiments, the method further includes the step: S8. Repeating steps S4-S7.
[0048] In this embodiment, if there is a need to further thicken the copper layer, steps S4-S7 can be repeated.
[0049] In some embodiments, in step S3, the spray pressure of the spray etching is 0.2-0.4 MPa, the temperature is 45-55°C, and the etching time is 2-4 minutes.
[0050] In this embodiment, the microcapsules can rupture under the conventional spray pressure of 0.2-0.4 MPa in the PCB etching production line. The microcapsules will not rupture when the pressure is too low, and the microcapsules may rupture before reaching the copper surface when the pressure is too high. The etching rate decreases when the etching temperature is below 45°C, and the hydrochloric acid volatilization intensifies and the stability of the etching solution decreases when the temperature is above 55°C.
[0051] This application provides a small-pitch thick copper plate, wherein the thickness of the copper plate is greater than or equal to 70 μm and the pitch is less than or equal to 150 μm.
[0052] In some embodiments, the total copper thickness of the outer layer is >150μm, the copper thickness of the first etching in S3 is 80~100μm, and the copper plating thickness in S6 is >70μm. The spacing is less than or equal to 150μm.
[0053] Source of raw materials All raw materials used in this application are commercially available industrial-grade or analytical-grade products, which can be obtained through conventional commercial channels.
[0054] The first microcapsule was prepared as follows: 10.0 g of β-cyclodextrin-polyethylene glycol (β-CD-PEG) was dissolved in 100 mL of deionized water and stirred in a 40°C water bath until completely dissolved, preparing a β-CD-PEG aqueous solution with a mass percentage concentration of approximately 9.1%, which served as the inner aqueous phase (W1). Separately, 1.2 g of sodium alginate was dissolved in 100 mL of deionized water and heated and stirred in a 60°C water bath until completely dissolved, preparing a sodium alginate aqueous solution with a mass percentage concentration of approximately 1.2%, which served as the outer aqueous phase (W2). 1.5 g of Tween-80 (accounting for approximately 1.5% of the outer aqueous phase mass) was added and stirred until homogeneous. 30 mL of liquid paraffin was measured as the oil phase. The inner aqueous phase was slowly added to the oil phase at a stirring speed of 8000 r / min, with a volume ratio of inner aqueous phase to oil phase of 1:5, and emulsification was continued for 45 seconds to form a W1 / O type primary emulsion. The pre-emulsion was slowly added to the external aqueous phase at a stirring speed of 3000 r / min, with a volume ratio of pre-emulsion to external aqueous phase of 1:5. Emulsification was continued for 60 seconds to form a W1 / O / W2 type double emulsion. 20 mL of a 2.0% (w / w) calcium chloride aqueous solution was slowly added dropwise to the resulting double emulsion while stirring. The molar ratio of calcium ions to carboxyl groups in sodium alginate was 0.2:1. Stirring was continued at room temperature for 30 minutes to allow sodium alginate to crosslink and solidify with calcium ions at the oil-water interface, forming a calcium alginate capsule wall. After crosslinking, the capsule was centrifuged at 10000 rpm for 10 minutes. The precipitate was washed four times with deionized water and dried to constant weight in a vacuum drying oven at 45℃ to obtain the first microcapsule product. Scanning electron microscopy showed an average particle size of 1.2 μm, and transmission electron microscopy showed an average wall thickness of 120 nm.
[0055] The second microcapsule was prepared as follows: 1.26 g of copper peroxide (CuO2, 0.0132 mol) powder was weighed as the core material (the amount of copper peroxide was calculated as 1.5 times the molar amount of β-cyclodextrin units). 5.0 g of polyethylene glycol (PEG, molecular weight 10000) and 1.26 g of copper peroxide powder were premixed at a mass ratio of approximately 4:1, added to 150 mL of deionized water, and heated and stirred in a 70℃ water bath until the polyethylene glycol was completely dissolved, forming a uniform PEG / CuO2 mixed suspension. Under a stirring speed of 250 r / min, 50 mL of 20% sodium sulfate aqueous solution was added dropwise as a coagulant to the above mixed suspension, and stirring was continued for 45 minutes, allowing the polyethylene glycol to gradually precipitate on the surface of the copper peroxide and coagulate into the capsule wall. After coagulation, the system was naturally cooled to room temperature, and stirring was continued for 15 minutes to fully solidify the capsule wall. The obtained microcapsule suspension was centrifuged (5000 rpm, 12 minutes), and the precipitate was washed four times with deionized water and dried to constant weight in a vacuum drying oven at 45℃ to obtain the second microcapsule product. The average particle size was measured to be 1.5 μm by scanning electron microscopy, and the average wall thickness was measured to be 150 nm by transmission electron microscopy.
[0056] The following specific embodiments further illustrate this solution.
[0057] Example 1 A method for preparing a fine-pitch thick copper plate using an etching solution includes the following steps: S1. The substrate is an FR-4 grade copper-clad laminate with an initial base copper thickness of 17μm and a target finished copper thickness of 70μm (2oz). The designed linewidth / spacing is 75μm / 75μm. A copper sulfate electroplating solution is used with a current density of 2.2A / dm³. 2 The electroplating time is 75 minutes, the plating solution temperature is 25±2℃, and the plating solution uniformity is maintained by circulating filtration and air stirring during the electroplating process. After the first whole board electroplating, the copper layer thickness is increased from 17μm to 35μm. After the electroplating is completed, it is washed with water, acid-washed and dried. S2. Apply a 50μm thick photosensitive dry film to the plate surface and pass it through a process at 110℃ and 4kg / cm². 2 Hot-press roller coating is performed at a speed of 1.5 m / min. After coating, the board surface is exposed to circuit patterns using an exposure machine with an exposure energy of 70 mJ / cm². 2 After exposure, the area is developed with 1wt% sodium carbonate solution at a development temperature of 30±2℃ for 50 seconds to remove the dry film from the unexposed area, exposing the gap area (75μm wide) that needs to be etched away. The circuit pattern area is covered and protected by the dry film. After development, the area is washed with water and dried. S3. Using the prepared etching solution, etching is performed on a horizontal spray etching line. The spray pressure is 0.3MPa, the etching temperature is 50℃, and the spray angle is 90°. The spray etching equipment is a horizontal spray etching line with independent pressure supply for the upper and lower spray pipes. The nozzles are conical nozzles, arranged in an alternating pattern. After the 35μm copper layer in the exposed gap area is completely removed by etching, the film is stripped using a 4wt% sodium hydroxide solution at a temperature of 50℃. The dry film protective layer on the circuit surface is peeled off, exposing the 35μm half-thick copper circuit formed by the first electroplating. After stripping, the circuit is washed with water, acid-washed, and dried. S4. Epoxy resin is filled into the etched gaps using a vacuum filling machine. Before filling, the board surface is pre-baked at 100℃ for 10 minutes to remove moisture. The vacuum degree is ≤-0.095MPa, the filling pressure is 0.5MPa, and the pressure is held for 70 seconds. After filling, the board is heat-cured at 150℃ for 60 minutes to ensure complete cross-linking and curing of the resin. The cured board surface is then polished using a non-woven fabric brush polisher at a pressure of 6N / cm. 2 The grinding wheel speed is 250 rpm, the linear speed is 1.5 m / min, and the plate is ground until the resin surface is flush with the copper surface. The surface roughness Ra < 0.1 μm. During the grinding process, the single grinding amount is controlled not to exceed 10 μm to avoid excessive wear of the copper layer. After grinding, the plate is washed with water and dried. S5. Then, a 50μm thick photosensitive dry film is applied to the material obtained in step S4. The film application, exposure, and development process conditions are the same as in S2. After development, the dry film covers and protects all the gap areas filled with resin, while exposing the circuit pattern that needs to be thickened with copper. After development, it is washed with water and dried. S6. A copper sulfate-based pattern plating solution was used, with a current density of 3.0 A / dm³. 2 The electroplating time is 90 minutes, which increases the copper thickness of the exposed circuit area from 35μm to 70μm; S7. After electroplating, the film is removed using a 4wt% sodium hydroxide solution at 50℃, peeling off the second dry film protective layer. After removal, the product is washed with water, acid-washed, and dried to obtain the finished thick copper small-pitch circuit board. Figure 2 As shown; The etching solution preparation method for step S3 is as follows: Weigh 190g of copper chloride and dissolve it in approximately 700mL of deionized water, stirring until completely dissolved; slowly add 2.0g of hydrochloric acid (37%) under stirring, stirring until homogeneous; add 6.0g of benzotriazole (BTA), stirring until completely dissolved; add 0.5g of polyethylene glycol (PEG-600, surfactant), 0.4g of triethanolamine (dispersant), 0.2g of sodium 2-ethylhexanol sulfate (wetting agent), and 1.0g of urea (stabilizer), stirring until homogeneous; finally, add 3.0g of the first microcapsule and 3.0g of the second microcapsule, stirring at 200rpm for 20min to ensure uniform dispersion of the microcapsules; add deionized water to 1L, and continue stirring at low speed for 10min to obtain the etching solution.
[0058] Example 2 A method for processing a small-pitch thick copper plate is the same as in Example 1, except that the amount of the first microcapsule is 4g and the amount of the second microcapsule is 2g.
[0059] Example 3 A method for processing a small-pitch thick copper plate is the same as in Example 1, except that the amount of the first microcapsule is 2g and the amount of the second microcapsule is 4g.
[0060] Comparative Example 1 A method for processing a small-pitch thick copper plate is the same as in Example 1, except that the first microcapsule is not added to the etching solution.
[0061] Comparative Example 2 A method for processing a small-pitch thick copper plate is the same as in Example 1, except that the second microcapsule is not added to the etching solution.
[0062] Comparative Example 3 A method for processing a small-pitch thick copper plate is the same as in Example 1, except that the first microcapsule and the second microcapsule are not added to the etching solution.
[0063] Comparative Example 4 A method for processing a small-pitch thick copper plate is the same as in Example 1, except that benzotriazole is not added to the etching solution.
[0064] Comparative Example 5 A method for processing a small-pitch thick copper plate is the same as in Example 1, except that the amount of the first microcapsule is 5g and the amount of the second microcapsule is 1g.
[0065] Testing and Evaluation The etching rate and lateral etching amount of the small-pitch thick copper plates obtained from different embodiments and comparative examples were measured, and the results are shown in Table 1.
[0066] Etching rate determination: The weight loss method was used, and the etching area was S (mm²). 2 The etching time is t (min), the mass difference before and after etching is Δm (mg), and the copper density is 8.93 g / cm³. 3 Etching rate u = Δm / (S × 8.93 × t) × 10 -3 (μm / min); Lateral etching measurement: After etching, the circuit board is sampled, embedded with resin, and polished. The cross-section of the circuit is observed using a scanning electron microscope (SEM). The top width (Wt) and bottom width (Wb) of the circuit are measured. Lateral etching amount = (Wt-Wb) / 2 (μm). Five circuits are randomly selected for measurement, and the average value is taken.
[0067] Table 1 Measurement Results
[0068] As shown in Table 1, this application combines BTA corrosion inhibitor with two types of microcapsules in the same etching solution. During spray etching, the spray flow vertically impacts the bottom of the circuit, causing the two types of microcapsules to rupture in situ at the bottom. This relieves the inhibition of bottom etching by the corrosion inhibitor while maintaining a high etching rate on the bottom copper surface. Meanwhile, the sidewalls of the circuit are scoured by the parallel spray flow, keeping the microcapsules intact and preventing rupture. BTA can then be continuously adsorbed onto the sidewall copper surface to exert its corrosion inhibitor effect. Thus, high-speed bottom etching and side etching control are achieved in the same etching step, ultimately resulting in a thick copper small-pitch PCB product.
[0069] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for processing small-pitch thick copper plates, characterized in that, Includes the following steps: S1. Provide copper-clad laminate substrate, drill holes in the substrate, perform copper plating, and perform the first full-board electroplating; S2. Perform the first pattern transfer, apply the first dry film to the board surface, and after exposure and development, retain the dry film on the circuit pattern to expose the gap area that needs to be etched away. S3. Use an etching solution to perform spray etching and remove the first dry film; S4. Fill the etched gaps with insulating resin, cure it, and grind it smooth; S5. Perform a second pattern transfer, apply a second dry film, and after exposure and development, the dry film covers the gap area, exposing the circuit pattern; S6. Perform the second pattern electroplating; S7. Remove the second dry film to obtain the small-pitch thick copper plate; The etching solution comprises the following components in parts by weight: 180-200 parts copper chloride, 1.8-2.5 parts hydrochloric acid, 4-8 parts benzotriazole corrosion inhibitor, 1-5 parts first microcapsule, 1-5 parts second microcapsule, 0.3-0.7 parts surfactant, 0.2-0.6 parts dispersant, 0.1-0.3 parts wetting agent, and 0.5-2.0 parts stabilizer; the core material of the first microcapsule contains β-cyclodextrin-polyethylene glycol; and the core material of the second microcapsule contains copper peroxide.
2. The processing method for small-pitch thick copper plates according to claim 1, characterized in that, The molar ratio of β-cyclodextrin-polyethylene glycol (based on β-cyclodextrin units) in the first microcapsule core material to copper peroxide in the second microcapsule core material is 1:1-2.
3. The processing method for small-pitch thick copper plates according to claim 1, characterized in that, The wall material of the first microcapsule is calcium alginate, and the wall material of the second microcapsule is polyethylene glycol.
4. The processing method for small-pitch thick copper plates according to claim 1, characterized in that, The surfactant is polyethylene glycol; the dispersant is triethanolamine; the wetting agent is sodium 2-ethylhexanol sulfate; and the stabilizer is urea.
5. The processing method for small-pitch thick copper plates according to claim 1, characterized in that, The first microcapsule was prepared by using a β-cyclodextrin-polyethylene glycol aqueous solution as the inner aqueous phase and a sodium alginate aqueous solution as the outer aqueous phase, via a double emulsion-calcium ion crosslinking method.
6. The processing method for small-pitch thick copper plates according to claim 1, characterized in that, The second microcapsule is prepared by using copper peroxide as the core material, polyethylene glycol as the wall material, and sodium sulfate aqueous solution as the coagulant, through a single coagulation method.
7. The processing method for small-pitch thick copper plates according to claim 1, characterized in that, It also includes the step: S8. Repeat steps S4-S7.
8. The processing method for small-pitch thick copper plates according to claim 7, characterized in that, In step S3, the spray pressure of the spray etching is 0.2-0.4 MPa, the temperature is 45-55℃, and the etching time is 2-4 minutes.
9. A small-pitch thick copper plate obtained by the processing method according to any one of claims 1-8.
10. The small-pitch thick copper plate according to claim 9, characterized in that, The copper plates have a thickness of ≥70μm and a spacing of ≤150μm.